Education Quality and Economic Growth - World Bank (The World Bank, 2007)
This book aims to contribute to the World Bank's education agenda by communicating research findings on the impact of education quality on economic growth. Eric Hanushek and Ludger Wößmann show that indeed the quality of education, rather than mere access to education, is what impacts economic growth. These world-renowned researchers use data on economic growth and student cognitive skills to help shift the dialogue to the ever-pressing issue of education quality